Factors Affecting Aggressiveness in Adolescents and Young Adults: A Systematic Review of the Literature 2020-2024 - Nofriansyah, Muh. Fauzan; Suhadianto, Suhadianto (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
Aggression is a form of deviant behaviour that has a negative impact on individuals and their social environment. This study aims to systematically examine the factors that influence aggression behaviour by analysing 13 literature studies from 2020 to 2024. The results show that internal factors such as emotional intelligence, self-control, emotional maturity, impulsivity, and cognitive impairment have a significant relationship with the emergence of aggression. In addition, external factors such as family communication patterns, peer influence, school environment, digital media, culture and childhood traumatic experiences also influence aggressive behaviour. This study confirms that aggression is the result of multidimensional interactions between personal and contextual factors. An integrative and evidence-based approach is needed for effective interventions. The findings are expected to serve as a reference in designing aggression prevention and treatment programmes among adolescents and young adults.